Low expansion, wear-resistant, high light transmittance, dense seam and continuous grain ceramic rock plate and preparation method thereof

By using a combination of specially developed translucent blank, translucent glaze and low-expansion protective glaze in the preparation of ceramic rock slabs, the deformation and glaze defects of densely-slit-connected ceramic products are solved, and low-expansion resistance is achieved Grinding, high light transmission effect and reduce costs.

CN118791325BActive Publication Date: 2025-01-17MONALISA GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411275155.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-17
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing densely-slit-connected ceramic products are difficult to prevent deformation and glaze defects in the preparation process, and the high price of lithium-containing mineral raw materials, resulting in an increase in formula costs.

Method used

Using a combination of specially developed light-transmitting blank, light-transmitting glaze and low-expansion protective glaze, the design pattern is printed by inkjet and polished at high temperature to prepare low-expansion and wear-resistant high-transmitting dense seam connection ceramics. Rock slab.

Benefits of technology

On the premise of avoiding deformation and glaze defects, high-transparent dense seam jointed ceramic rock slabs with low expansion and wear resistance are obtained, which reduces the moisture absorption expansion of the product and brick deformation, and improves the light transmission performance and color development effect. Reduced costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791325B_ABST
    Figure CN118791325B_ABST
Patent Text Reader

Abstract

The present invention relates to a low expansion, wear-resistant, high light transmittance, dense seam and continuous pattern ceramic rock plate and a preparation method thereof, and belongs to the technical field of ceramic tile production and manufacturing. The preparation method comprises: preparing a light-transmitting powder into a light-transmitting blank and applying a light-transmitting glaze on the surface of the light-transmitting blank; inkjet printing a design pattern on the surface of the blank after applying the light-transmitting glaze; applying a low expansion protective glaze on the surface of the blank after the inkjet printing of the design pattern; sintering and polishing the blank after applying the low expansion protective glaze to obtain the low expansion, wear-resistant, high light transmittance, dense seam and continuous pattern ceramic rock plate. The present invention obtains a low expansion, wear-resistant, high light transmittance, dense seam and continuous pattern ceramic rock plate under the premise of avoiding deformation and glaze defects by using a specially developed light-transmitting blank, a light-transmitting glaze and a low expansion protective glaze in combination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-expansion, wear-resistant, high-light-transmittance, dense-seam, continuous-grain ceramic rock plate and a preparation method thereof, belonging to the technical field of ceramic tile production and manufacturing. Background Art

[0002] Ceramic tiles are a traditional decorative product in the field of architectural ceramics. They are loved by consumers for their excellent wear resistance, anti-fouling properties and ever-changing decorative effects. With the development of the economy, people have a higher pursuit of quality of life, and ceramic tiles with both aesthetics and practical value are favored by consumers. Among them, high-transmittance dense-seam continuous-grain ceramic rock slabs are elegant and generous, and can present pattern textures under the irradiation of light, thereby enhancing the overall decorative effect. They have a large application space in the field of building materials and decoration. However, dense-seam continuous-grain ceramic products also put forward higher requirements on their preparation process. Among them, how to prevent the deformation and glaze defects of dense-seam continuous-grain products is one of the important issues that need to be overcome.

[0003] The close-seam continuous-grain low-expansion coefficient floor heating tile disclosed in Chinese patent CN 114988857A includes a body layer and a glaze layer from bottom to top; wherein the body layer includes the following components in mass fractions: 20-25 parts of feldspar, 12-16 parts of quartz, 12-16 parts of clay, 12-16 parts of mineral salt, 6-8 parts of bauxite, and 20-40 parts of lithium-containing ceramic powder; the glaze layer includes the following components in mass fractions: 25-43 parts of feldspar, 18-23 parts of quartz, 13-20 parts of clay, 7-11 parts of calcined alumina, 1-4 parts of nepheline, 3-5 parts of burned talc, and 2-5 parts of frit; the lithium-containing ceramic powder contains at least one of spodumene, petalite, and lithium porcelain stone; the feldspar of the glaze layer is mainly composed of the following components in mass fractions: 28-33 parts of petalite and 7-10 parts of albite. It can be seen that CN 114988857A mainly uses spodumene, lithium porcelain stone, etc. to reduce the thermal expansion coefficient of ceramic products. However, the price of lithium-containing mineral raw materials is high, resulting in a significant increase in formulation costs. Summary of the invention

[0004] In view of the above problems, the present invention provides a low-expansion, wear-resistant, high-light transmittance, dense-seam and connected ceramic rock plate and a preparation method thereof. By using a specially developed translucent blank, a translucent surface glaze and a low-expansion protective glaze in combination, a low-expansion, wear-resistant, high-light transmittance, dense-seam and connected ceramic rock plate is obtained while avoiding deformation and glaze defects.

[0005] In a first aspect, the present invention provides a method for preparing a low-expansion, wear-resistant, high-transmittance, dense-seam, and continuous-grain ceramic rock plate. The preparation method comprises:

[0006] preparing a light-transmitting powder into a light-transmitting green body;

[0007] Applying a translucent glaze on the surface of the translucent blank;

[0008] inkjet printing a design pattern on the surface of the body after the transparent glaze is applied;

[0009] Applying a low expansion protective glaze on the surface of the blank after the inkjet printing of the design pattern;

[0010] The green body to which the low expansion protective glaze is applied is fired and polished to obtain the low expansion wear-resistant high light transmittance dense seam continuous pattern ceramic rock plate.

[0011] Preferably, the mineral composition of the translucent glaze includes, by mass percentage, 40-60% washed kaolin, 20-30% potassium feldspar, 5-15% high-aluminum and high-calcium frit, 5-15% barium carbonate, and 1-10% wollastonite; wherein the chemical composition of the high-aluminum and high-calcium frit includes, by mass percentage, IL: 1-10%, SiO2: 35-65%, Al2O3: 20-30%, Fe2O3: 0.02-0.10%, TiO2: 0.01-0.05%, CaO: 10-23%, MgO: 0.5-3%, K2O: 1-8%, Na2O: 1-10%, and BaO: 0.1-3%.

[0012] Preferably, the chemical composition of the translucent glaze includes, by mass percentage, IL: 4~6%, SiO2: 55~65%, Al2O3: 19~22%, Fe2O3: 0.01~0.1%, TiO2: 0.01~0.1%, CaO: 3~5%, MgO: 0.1~0.5%, K2O: 2~3%, Na2O: 1~3%, and BaO: 7~9%.

[0013] Preferably, the thermal expansion coefficient of the transparent glaze at 40-600°C is 6.5×10 -6 / K ~6.8×10 -6 / K.

[0014] Preferably, the mineral composition of the low expansion protective glaze includes, by mass percentage, kaolin 8-12%, burned talc 10-18%, low expansion frit 45-55%, barium carbonate 5-20%, wollastonite 10-18%, and calcined zinc oxide 1-3%; wherein the chemical composition of the low expansion frit includes, by mass percentage, IL: 0.1-0.5%, SiO2: 47-54%, Al2O3: 10-16%, Fe2O3: 0.01-0.05%, TiO2: 0.01-0.05%, CaO: 5-10%, MgO: 1-3%, K2O+Na2O: 3-6%, BaO: 8-12%, and ZnO: 10-15%.

[0015] Preferably, the chemical composition of the low expansion protective glaze includes, by mass percentage, IL: 3~4%, SiO2: 47~49%, Al2O3: 11~13%, Fe2O3: 0.01~0.2%, TiO2: 0.01~0.05%, CaO: 11~14%, MgO: 4~6%, K2O: 1~3%, Na2O: 1~2%, BaO: 8~10%, and ZnO: 4~6%.

[0016] Preferably, the thermal expansion coefficient of the low expansion protective glaze at 40-600°C is 6.0×10 -6 / K ~6.2×10 -6 / K.

[0017] Preferably, the light-transmitting glaze is applied by spraying; the specific gravity of the light-transmitting glaze is 1.4-1.5 g / cm 3 , glaze application amount is 540~700g / m 2 .

[0018] Preferably, the low expansion protective glaze is applied by spraying; the specific gravity of the low expansion protective glaze is 1.5-1.6 g / cm 3 , glaze application amount is 600~770g / m 2 .

[0019] Preferably, the mineral composition of the translucent powder includes, by mass percentage, 30-40% washed kaolin, 15-25% potassium feldspar, 25-35% high-aluminum and high-calcium frit, and 10-25% wollastonite; wherein the chemical composition of the high-aluminum and high-calcium frit includes, by mass percentage, IL: 1-10%, SiO2: 35-65%, Al2O3: 20-30%, Fe2O3: 0.02-0.10%, TiO2: 0.01-0.05%, CaO: 10-23%, MgO: 0.5-3%, K2O: 1-8%, Na2O: 1-10%, and BaO: 0.1-3%.

[0020] Preferably, the sintering temperature is 1190-1210° C., and the sintering time is 60-80 minutes.

[0021] In a second aspect, the present invention provides a low expansion, wear-resistant, high light transmittance ceramic rock plate with dense seams and continuous veins. The low expansion, wear-resistant, high light transmittance ceramic rock plate with dense seams and continuous veins is obtained according to the preparation method.

[0022] Beneficial Effects

[0023] The present invention uses a specially developed light-transmitting body, a light-transmitting surface glaze and a low-expansion protective glaze in combination, thereby obtaining a low-expansion, wear-resistant, high-light-transmitting, dense-seam, and continuous-grain ceramic rock slab while avoiding deformation and glaze defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a brick surface effect diagram of Example 1;

[0025] Figure 2 This is a comparison diagram of the light transmission effect of the light-transmitting glaze used in Example 1 (left) and the conventional zirconium white glaze used in Comparative Example 1 (right);

[0026] Figure 3 It is a comparison diagram of the brick surface effects of Example 3 (left) and Comparative Example 2 (right);

[0027] Figure 4 This is the brick surface effect diagram of Example 3;

[0028] Figure 5 This is the brick surface effect diagram of Example 4. DETAILED DESCRIPTION

[0029] The present invention is further described by the following embodiments, which should be understood to be only used to illustrate the present invention, but not to limit the present invention. The following is an exemplary description of the preparation method of the low expansion, wear-resistant, high light transmittance, dense seam and continuous pattern ceramic rock plate of the present invention.

[0030] The close seams of the close-seam continuous ceramic rock slab refer to the close-seam paving of tiles, specifically, controlling the gap between tiles within 0.5mm during the paving process, so that there is no obvious splicing boundary between the two tiles, and they are seamlessly integrated. Good close-seam paving is beneficial to the realization of the continuous effect of tiles. The flatness, expansion coefficient and water absorption rate of the tiles are the main factors affecting the close-seam continuous effect. Among them, the low expansion coefficient can effectively prevent the deformation of the tiles after paving, so that the close-seam continuous effect of the product is not affected by changes in external temperature, humidity, etc.

[0031] Prepare translucent powder (translucent blank). In some embodiments, the mineral composition of the translucent powder includes: by mass percentage, 30-40% washed kaolin, 15-25% potassium feldspar, 25-35% high-aluminum and high-calcium frit, and 20-25% wollastonite.

[0032] Among them, the chemical composition of the high-aluminum and high-calcium frit of the translucent powder includes, in mass percentage, IL: 1~10%, SiO2: 35~65%, Al2O3: 20~30%, Fe2O3: 0.02~0.10%, TiO2: 0.01~0.05%, CaO: 10~23%, MgO: 0.5~3%, K2O: 1~8%, Na2O: 1~10%, and BaO: 0.1~3%.

[0033] As an example, the chemical composition of the high-aluminum and high-calcium frit of the translucent powder includes, in mass percentage, IL: 1~3%, SiO2: 35~45%, Al2O3: 25~30%, Fe2O3: 0.02~0.10%, TiO2: 0.01~0.05%, CaO: 10~23%, MgO: 1~3%, K2O: 3~8%, Na2O: 1~10%, and BaO: 1~3%.

[0034] In some embodiments, the mineral composition of the high-aluminum and high-calcium frit includes, by mass percentage, 25-31% potassium feldspar, 34-42% wollastonite, 4-10% dolomite, 2-5% barium carbonate, and 20-24% calcined alumina. The raw materials are weighed according to the mineral composition of the high-aluminum and high-calcium frit, mixed evenly, and melted at 1400-1500° C. for 1-2 hours to obtain glass liquid, and the glass liquid is water quenched and crushed to obtain the high-aluminum and high-calcium frit.

[0035] The use of a large amount of wollastonite and high-aluminum and high-calcium frit in the light-transmitting powder has the advantages of increasing the calcium oxide and aluminum oxide content in the light-transmitting powder, and generating a large amount of main labradorite crystal phase inside the green body after high-temperature firing. The refractive index of labradorite is close to that of glass, which can reduce the loss of light due to scattering between the glass phase and the crystal phase. The inventor has tried to directly use wollastonite and aluminum oxide in the light-transmitting green body formula, and found that the labradorite crystal phase generated in the green body is relatively small, and aluminum oxide fails to effectively participate in the reaction of generating labradorite, but exists in the form of corundum, which increases the loss of light inside the green body. The present invention adopts the method of combining wollastonite and a special high-aluminum and high-calcium frit, which can not only increase the aluminum oxide content of the green body formula, increase the high-temperature viscosity, and reduce the high-temperature deformation, but also facilitate the generation of a more active and more abundant labradorite crystal phase, thereby improving the light transmission performance of the green body.

[0036] According to the formula of the light-transmitting powder, the raw materials are weighed, and water is added to carry out ball milling, spray granulation, aging, etc. to obtain the light-transmitting powder.

[0037] The light-transmitting powder is molded into a light-transmitting body. The molding method is not limited, and can be dry pressing molding. The light-transmitting body is dried. For example, the drying temperature is 180-220° C., and the drying time is 40-60 minutes.

[0038] In some embodiments, the chemical composition of the light-transmitting blank includes, by mass percentage, IL: 3~5%, SiO2: 52~57%, Al2O3: 19~22%, Fe2O3: 0.01~0.1%, TiO2: 0.01~0.1%, CaO: 11~15%, MgO: 0.01~1.0%, K2O: 1~5%, Na2O: 1~4%, and BaO: 0.3~1.0%.

[0039] The thermal expansion coefficient of the transparent body at 40-600°C is 6.1×10 -6 / K ~6.3×10 -6 / K.

[0040] The present invention uses low-iron and low-titanium clay and flux raw materials in the light-transmitting green body formula, and adds a special high-aluminum and high-calcium frit on the basis of wollastonite, which not only increases the calcium oxide and aluminum oxide content of the green body formula, but also generates a large amount of labradorite main crystal phase inside the green body after high-temperature sintering, thereby improving the light transmission performance of the green body.

[0041] A translucent glaze is applied on the surface of the translucent blank.

[0042] The mineral composition of the translucent glaze includes, by mass percentage, 40-60% washed kaolin, 20-30% potassium feldspar, 5-15% high-aluminum and high-calcium frit, 5-15% barium carbonate, and 1-10% wollastonite.

[0043] Among them, the chemical composition of the high-aluminum and high-calcium frit of the translucent glaze includes, in mass percentage, IL: 1~10%, SiO2: 35~65%, Al2O3: 20~30%, Fe2O3: 0.02~0.10%, TiO2: 0.01~0.05%, CaO: 10~23%, MgO: 0.5~3%, K2O: 1~8%, Na2O: 1~10%, and BaO: 0.1~3%.

[0044] For example, the chemical composition of the high-aluminum and high-calcium frit of the translucent glaze includes, in mass percentage, IL: 1~10%, SiO2: 35~65%, Al2O3: 20~30%, Fe2O3: 0.02~0.10%, TiO2: 0.01~0.05%, CaO: 10~23%, MgO: 0.5~3%, K2O: 1~5%, Na2O: 1~3%, and BaO: 0.1~3%.

[0045] The use of barium carbonate in the translucent glaze formula can promote the formation of barium feldspar crystal phase with a refractive index close to that of glass. Under the premise of ensuring the translucent performance of the glaze, the color development performance of the glaze is improved. At the same time, compared with conventional potassium sodium glass (8.5×10 -7 / ℃~10×10 -7 / ℃), the expansion coefficient of the celsium feldspar crystal phase (3.0×10 -7 / ℃) is small, which reduces the expansion coefficient of the glaze layer and is beneficial to increase the adaptability to the glaze body.

[0046] Moreover, due to the large amount of calcium oxide in the green body formula, the green body has poor color development for red ink and yellow ink. At the same time, due to the large amount of labradorite crystal phase (expansion coefficient 4.8×10-6 / ℃) results in a low expansion coefficient of the body. The present invention creatively develops a glaze formula with a low expansion coefficient, good light transmittance and good color development to match the light-transmitting body. By generating a barium feldspar crystal phase with a refractive index close to that of the glass phase in the glaze formula, the light transmittance and color development of the glaze are improved. At the same time, the expansion coefficient of the barium feldspar crystal phase is smaller than that of the conventional potassium-sodium glass, which reduces the expansion coefficient of the light-transmitting glaze layer and is conducive to increasing the adaptability to the body.

[0047] In some embodiments, the chemical composition of the translucent glaze includes, by mass percentage, IL: 4~6%, SiO2: 55~65%, Al2O3: 19~22%, Fe2O3: 0.01~0.1%, TiO2: 0.01~0.1%, CaO: 3~5%, MgO: 0.1~0.5%, K2O: 2~3%, Na2O: 1~3%, BaO: 7~9%.

[0048] The thermal expansion coefficient of the translucent glaze at 40-600°C is 6.5×10 -6 / K~6.8×10 -6 / K.

[0049] The application method of the light-transmitting glaze is not limited. The light-transmitting glaze can be applied by spraying. In some embodiments, the specific gravity of the light-transmitting glaze is 1.4-1.5 g / cm 3 , glaze application amount is 540~700g / m 2 If the amount of translucent glaze applied is too low, it cannot evenly cover the translucent body, resulting in direct contact between the inkjet pattern and the body at a local position, which is not conducive to the color development of the inkjet pattern; if the amount of translucent glaze applied is too high, the glaze layer will be thicker, which is not conducive to the water discharge of the glaze layer and is likely to increase the firing defects of the product. At the same time, too much glaze applied is not conducive to improving the effect, but reduces production efficiency.

[0050] The design pattern is printed on the surface of the blank after the transparent glaze is applied. The inkjet printing pattern decoration is carried out using a digital inkjet machine. The color and texture of the inkjet printed design pattern can be adaptively changed as needed.

[0051] Apply a low expansion protective glaze to the surface of the inkjet printed design.

[0052] The mineral composition of the low expansion protective glaze includes, by mass percentage, 8-12% kaolin, 10-18% calcined talc, 45-55% low expansion frit, 5-20% barium carbonate, 10-18% wollastonite, and 1-3% calcined zinc oxide.

[0053] The chemical composition of the low expansion frit includes, by mass percentage, IL: 0.1-0.5%, SiO2: 47-54%, Al2O3: 10-16%, Fe2O3: 0.01-0.05%, TiO2: 0.01-0.05%, CaO: 5-10%, MgO: 1-3%, K2O+Na2O (K2O and / or Na2O): 3-6%, BaO: 8-12%; ZnO: 10-15%.

[0054] The mineral composition of the low expansion frit includes: in terms of mass percentage, quartz 15-19%, kaolin 0-4% (preferably 1-4%), potassium feldspar 19-23%, sodium feldspar 13-17%, wollastonite 12-16%, dolomite 2-6%, zinc oxide 10-15%, barium carbonate 10-15%, and aluminum oxide 2-6%. Weigh the raw materials according to the mineral composition of the low expansion frit, mix them evenly, melt them at 1400-1500°C for 1-2 hours to obtain glass liquid, and quench the glass liquid with water, and crush it to obtain a low expansion frit. In some embodiments, the thermal expansion coefficient of the low expansion frit at 40-600°C is 5.4×10 -6 / K~5.6×10 -6 / K.

[0055] The expansion coefficient of conventional protective glaze is usually higher than that of the body. If conventional protective glaze is used, the glaze layer will be subjected to tension and cracks due to the mismatch in the expansion coefficients of the body and glaze. The present invention creatively develops a transparent protective glaze with a low expansion coefficient to match the translucent body and the translucent surface glaze. The low expansion protective glaze uses low expansion frit and raw materials such as barium carbonate to generate barium feldspar and labradorite crystal phases in the glaze layer. Since glass deformable components such as potassium feldspar and sodium feldspar are not used, the expansion coefficient of the protective glaze is ultimately reduced; at the same time, since labradorite and barium feldspar exist in the glaze layer, the glaze surface has more crystal phases after polishing, which greatly improves the wear resistance of the glaze surface.

[0056] In some embodiments, the chemical composition of the low expansion protective glaze includes, in mass percentage, IL: 3~4%, SiO2: 47~49%, Al2O3: 11~13%, Fe2O3: 0.01~0.2%, TiO2: 0.01~0.05%, CaO: 11~14%, MgO: 4~6%, K2O: 1~3%, Na2O: 1~2%, BaO: 8~10%, and ZnO: 4~6%.

[0057] The invention uses specially developed low expansion frit and barium carbonate in the formula of low expansion protective glaze. The low expansion frit has a low expansion coefficient and enters the glass phase to reduce the expansion coefficient of the protective glaze. At the same time, the introduction of barium carbonate promotes the formation of celsium feldspar and synergistically improves the wear resistance of the glaze surface with labradorite.

[0058] The thermal expansion coefficient of the low expansion protective glaze at 40-600°C is 6.0×10 -6 / K~6.2×10 -6 / K.

[0059] The low expansion protective glaze may be applied in any manner. For example, the low expansion protective glaze may be applied by spraying. In some embodiments, the specific gravity of the low expansion protective glaze is 1.5-1.6 g / cm 3 , glaze application amount is 600~770g / m 2 If the amount of protective glaze applied is too low, it will increase the difficulty of later polishing, and it is easy to "polish through the body", leaving the body exposed and the product performance substandard; if the amount of protective glaze applied is too high, it will not help improve the effect, but reduce production efficiency, and bubbles will be difficult to remove and easily form pore defects.

[0060] The inventors have tried to directly inkjet print the design pattern on the surface of the transparent body and apply a low expansion protective glaze. Although the ceramic rock slab prepared in this way did not have glaze cracks, the yellow and red areas of the inkjet design pattern had color differences on the transparent body, making it difficult to present the decorative effect of the inkjet design pattern.

[0061] The bricks with low expansion protective glaze are fired at high temperature, for example, at 1190~1210℃ for 60~80 minutes.

[0062] Polishing, grading, packaging and storage.

[0063] In summary, the present invention uses a specially developed translucent body, a translucent glaze and a low expansion protective glaze in combination, thereby obtaining a low expansion wear-resistant, high-transmittance, dense seam and continuous pattern ceramic rock plate under the premise of avoiding deformation and glaze defects. Among them, the present invention uses low-iron and titanium clay and high-aluminum and high-calcium frit raw materials, adopts a K-Na-Ca flux system, increases the calcium oxide and aluminum oxide content in the body formula, and generates a large amount of main crystalline phase of labradorite inside the translucent body after high-temperature firing. Moreover, in order to improve the color of the body and the matching with the body, the present invention has also developed a translucent glaze formula that matches the translucent body, and introduces barium feldspar crystal phase into the glaze composition of the translucent glaze without reducing the light transmission performance of the product, while achieving the purpose of improving the color performance, reducing the expansion coefficient of the translucent glaze and improving the adaptability to the body. In addition, the present invention has also developed a low expansion protective glaze using barium feldspar and labradorite to synergistically improve the wear resistance of the low expansion protective glaze and reduce the thermal expansion coefficient. The low expansion wear-resistant high light transmittance close-seam ceramic rock slab of the present invention has excellent light transmittance and good color development, which greatly reduces the late hygroscopic expansion and brick deformation of the close-seam ceramic rock slab. In some embodiments, referring to the standard GB / T 2680-2021, the visible light transmittance of the low expansion wear-resistant high light transmittance close-seam ceramic rock slab is 4.2% (5.5 mm).

[0064] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0065] Example 1

[0066] A method for preparing a low-expansion, wear-resistant, high-transmittance, dense-seam, continuous-grain ceramic rock plate comprises the following steps:

[0067] Step 1. Prepare the translucent powder into a translucent body. The mineral composition of the translucent powder includes, by mass percentage, 36% washed kaolin, 19% potassium feldspar, 26% high-aluminum high-calcium frit, and 19% wollastonite. Among them, the chemical composition of the high-aluminum high-calcium frit includes, by mass percentage, IL: 2.2%, SiO2: 39.89%, Al2O3: 27.4%, Fe2O3: 0.09%, TiO2: 0.02%, CaO: 12%, MgO: 1.7%, K2O: 5.8%, Na2O: 9.8%, BaO: 1.1%. The chemical composition of the light-transmitting blank includes, by mass percentage, IL: 4.8%, SiO2: 55.98%, Al2O3: 20.3%, Fe2O3: 0.1%, TiO2: 0.02%, CaO: 13.9%, MgO: 0.9%, K2O: 1.8%, Na2O: 1.6%, and BaO: 0.6%.

[0068] Step 2. Apply a translucent glaze on the surface of the translucent body. The mineral composition of the translucent glaze includes, by mass percentage, 50% washed kaolin, 25% potassium feldspar, 10% high-aluminum high-calcium frit, 10% barium carbonate, and 5% wollastonite. The chemical composition of the high-aluminum high-calcium frit includes, by mass percentage, IL: 2.2%, SiO2: 39.89%, Al2O3: 27.4%, Fe2O3: 0.09%, TiO2: 0.02%, CaO: 12%, MgO: 1.7%, K2O: 5.8%, Na2O: 9.8%, and BaO: 1.1%. The chemical composition of the translucent glaze includes, by mass percentage, IL: 5.7%, SiO2: 57.58%, Al2O3: 21%, Fe2O3: 0.1%, TiO2: 0.02%, CaO: 3.7%, MgO: 0.3%, K2O: 2.1%, Na2O: 1.8%, BaO: 7.7%. The translucent glaze is applied by spraying. The specific gravity of the translucent glaze is 1.4g / cm 3 , glaze application amount is 620g / m 2 .

[0069] Step 3. Inkjet print the design pattern on the surface of the blank after applying the translucent glaze.

[0070] Step 4. Apply low expansion protective glaze on the surface of the inkjet printed design. The mineral composition of the low expansion protective glaze includes: by mass percentage, kaolin 10%, calcined talc 15%, low expansion frit 51%, barium carbonate 8%, wollastonite 15%, calcined zinc oxide 1%. Among them, the chemical composition of the low expansion frit includes: by mass percentage, IL: 0.2%, SiO2: 50.75%, Al2O3: 13%, Fe2O3: 0.03%, TiO2: 0.02%, CaO: 8%, MgO: 1%, K2O+Na2O: 5%, BaO: 10%; ZnO: 12%. The chemical composition of the low expansion protective glaze includes, by mass percentage, IL: 3.4%, SiO2: 48.5%, Al2O3: 12.4%, Fe2O3: 0.17%, TiO2: 0.03%, CaO: 12.4%, MgO: 5.2%, K2O: 1.9%, Na2O: 1.2%, BaO: 9.6%, ZnO: 5.2%. The low expansion protective glaze is applied by spraying. The specific gravity of the low expansion protective glaze is 1.5g / cm 3 , glaze application amount is 680g / m 2 .

[0071] Step 5. The green body with low expansion protective glaze applied is fired and polished to obtain the low expansion wear-resistant high light transmittance dense seam continuous pattern ceramic rock plate. The firing temperature is 1190° C. and the firing time is 60 minutes.

[0072] Figure 1 This is the brick surface effect diagram of Example 1. It can be seen that the product has excellent light transmission performance, the light appears white after passing through, and the paving effect of the product reaches the requirements of dense seam paving.

[0073] The water absorption, wear resistance and hardness were tested in accordance with GB / T 39156-2020 "Technical Requirements and Test Methods for Large-Sized Ceramic Plates". According to the test results, the water absorption of the low-expansion, wear-resistant, high-transmittance, dense-seam, continuous-grain ceramic rock plate prepared in Example 1 was less than 0.1wt%, the wear resistance revolution number was 2100 revolutions, and the hardness was level 4.

[0074] Example 2

[0075] It is basically the same as Example 1, except that the chemical composition of the high-aluminum and high-calcium frit includes, by mass percentage, IL: 4.8%, SiO2: 56.18%, Al2O3: 20.3%, Fe2O3: 0.1%, TiO2: 0.02%, CaO: 13.9%, MgO: 0.9%, K2O: 1.8%, Na2O: 1.6%, and BaO: 0.4%.

[0076] Comparative Example 1

[0077] The invention is basically the same as Example 1, except that the light-transmitting glaze is replaced by a conventional zircon white glaze. The mineral composition of the conventional zircon white glaze includes, by mass percentage, kaolin 30%, potassium feldspar 35%, sodium feldspar 8%, calcined alumina 3%, calcined kaolin 15%, and zirconium silicate 9%. The chemical composition of the conventional zircon white glaze includes, by mass percentage, IL: 3.5%, SiO2: 55.8%, Al2O3: 27.5%, Fe2O3: 0.4%, TiO2: 0.2%, CaO: 0.2%, MgO: 0.1%, K2O: 4.3%, Na2O: 2.1%, and ZrO2: 5.9%.

[0078] Figure 2 This is a comparison chart of the light transmission effects of the light-transmitting glaze used in Example 1 (left) and the conventional zirconium white glaze used in Comparative Example 1 (right). The light-transmitting glaze of Example 1 and the conventional zirconium white glaze of Comparative Example 1 are applied to the surface of the green body sample respectively and then fired to obtain the test samples. It can be seen that the light transmittance of the conventional zirconium white glaze is significantly reduced (the glaze surface turns yellow). This is because the conventional zirconium white glaze achieves the effect of covering the base color defects of the green body and improving the whiteness by adding a certain amount of zirconium silicate. The refractive index of the zircon formed is relatively large, resulting in poor light transmission performance of the surface glaze layer or even basically no light transmission. Moreover, the ceramic rock plate prepared in Comparative Example 1 will have glaze cracking.

[0079] Comparative Example 2

[0080] The invention is basically the same as Example 1, except that a different inkjet printing design pattern is used, and the low expansion protective glaze is replaced by a common protective glaze. The mineral composition of the common protective glaze includes, by mass percentage, kaolin 10%, potassium feldspar 26%, sodium feldspar 18%, calcite 13%, calcite 15%, barium carbonate 9%, calcined kaolin 6%, and zinc oxide 3%. The chemical composition of the common protective glaze includes, by mass percentage, IL: 8.7%, SiO2: 48.8%, Al2O3: 14.3%, Fe2O3: 0.2%, TiO2: 0.1%, CaO: 7.5%, MgO: 4.8%, K2O: 2.9%, Na2O: 2.9%, BaO: 6.9%, and ZnO: 2.9%.

[0081] Example 3

[0082] It is basically the same as Comparative Example 2, except that the ordinary protective glaze is replaced by the low expansion protective glaze of Example 1.

[0083] Figure 3This is a comparison of the brick surface effects of Example 3 (left) and Comparative Example 2 (right). It can be seen that the ceramic rock board prepared in Comparative Example 2 has glaze cracking, and the light transmittance has not changed significantly. This is because potassium feldspar and sodium feldspar are used in large quantities in the ordinary protective glaze formula. Since potassium and sodium are not glass-forming elements, they will replace Si-O bonds in the glaze formula, thereby destroying the glass network structure and increasing the expansion coefficient of the glass phase, resulting in a larger expansion coefficient of the protective glaze and much greater than that of the light-transmitting body. The glaze layer is subjected to tensile stress, which leads to glaze cracking.

[0084] The inventors also found that when the translucent glaze was replaced with conventional zirconium white glaze and the low-expansion protective glaze was replaced with ordinary protective glaze, glaze cracks appeared in the prepared ceramic rock slabs and the light transmittance decreased significantly.

[0085] Comparative Example 3

[0086] It is basically the same as Example 1, except that a different inkjet printing design pattern is used, and the low expansion frit is replaced by a boron frit. The mineral composition of the low expansion protective glaze includes, by mass percentage, kaolin 10%, burnt talc 15%, boron frit 51%, barium carbonate 8%, wollastonite 15%, calcined zinc oxide 1%. The chemical composition of the boron frit includes, by mass percentage, SiO2: 58.9%, Al2O3: 12.1%, CaO: 4%, MgO: 1%, K2O+Na2O: 8%, BaO: 2%, ZnO: 2%, B2O3: 12%. The chemical composition of the low expansion protective glaze includes, by mass percentage, IL: 3.4%, SiO2: 52.6%, Al2O3: 9.6%, Fe2O3: 0.2%, TiO2: 0.1%, CaO: 9.0%, MgO: 5.2%, K2O: 2.5%, Na2O: 2.1%, BaO: 7.2%, ZnO: 2%, and B2O3: 6.1%.

[0087] Figure 4 This is the brick surface effect diagram of comparative example 3. It can be seen that although the expansion coefficient of the low expansion protective glaze using the boron frit is reduced, a large number of bubbles appear in the protective glaze layer due to the strong fluxing effect of the boron frit, which also causes the anti-fouling and other related properties of the glaze surface of the product after polishing to be substandard.

[0088] Comparative Example 4

[0089] It is basically the same as Example 1, except that a different inkjet printing design pattern is used, and the barium carbonate of the translucent glaze is replaced by wollastonite. The mineral composition of the translucent glaze includes: by mass percentage, 50% washed kaolin, 25% potassium feldspar, 10% high aluminum and high calcium frit, and 15% wollastonite. The chemical composition of the translucent glaze includes: by mass percentage, IL: 6.0%, SiO2: 55.2%, Al2O3: 22.9%, Fe2O3: 0.2%, TiO2: 0.1%, CaO: 7.8%, MgO: 0.4%, K2O: 4.1%, Na2O: 1.1%, ZnO: 1.2%, BaO: 1.0%.

[0090] Figure 5 This is the brick surface effect diagram of comparative example 4. It can be seen that although the translucent glaze uses high-aluminum and high-calcium frit, the red and yellow inks do not shine well on the glaze because the glaze formula contains more calcium oxide.

[0091] Comparative Example 5

[0092] It is basically the same as Example 1, except that the high-aluminum and high-calcium frit of the light-transmitting powder is replaced with a high-silicon frit. The mineral composition of the light-transmitting powder includes: by mass percentage, 30% washed kaolin, 17% potassium feldspar, 38% high-silicon frit, 4% burned talc, and 11% wollastonite. The chemical composition of the high-silicon frit includes: by mass percentage: SiO2: 91%, Al2O3: 2%, CaO: 2%, MgO: 1%, K2O: 1%, Na2O: 3%. The chemical composition of the light-transmitting powder includes: by mass percentage, IL: 3.5%, SiO2: 73.3%, Al2O3: 12%, Fe2O3: 0.1%, TiO2: 0.1%, CaO: 6.1%, MgO: 1.9%, K2O: 1.2%, Na2O: 1.8%.

[0093] Although clinker frit is used in the transparent body formula, the high quartz content of the whole formula leads to a large expansion coefficient of the body (10.5×10 -6 / K), which is much larger than the expansion coefficient of the light-transmitting blank in Example 1, and cannot meet the demand for products with dense seams and continuous patterns.

[0094] The light transmittance is tested with reference to the standard GB / T 2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet transmittance and related window glass parameters of architectural glass". The body expansion coefficient is tested with reference to the standard GB / T 3810.8-2016 "Test methods for ceramic tiles Part 8: Determination of linear thermal expansion". The color development is judged based on whether the inkjet printed design pattern on the surface of the ceramic rock plate is consistent with the design layout. The anti-fouling performance is tested with reference to the standard GB / T 3810.14-2016 "Test methods for ceramic tiles Part 14 Determination of anti-fouling". The product performance of each embodiment and comparative example is summarized in Table 1.

[0095] Table 1

[0096]

[0097] It can be seen from the above table that the present invention obtains low-expansion, wear-resistant, high-transmittance, dense-seam, and continuous-grain ceramic rock slabs while avoiding deformation and glaze defects by using a specially developed translucent body, a translucent surface glaze, and a low-expansion protective glaze in combination.

Claims

1. A method for preparing a low expansion, wear-resistant, high light transmittance, dense seam and continuous pattern ceramic rock plate, characterized in that: The preparation method comprises: The light-transmitting powder is prepared into a light-transmitting blank; the mineral composition of the light-transmitting powder includes, by mass percentage, 30-40% washed kaolin, 15-25% potassium feldspar, 25-35% high-aluminum high-calcium frit, and 10-25% wollastonite; wherein the chemical composition of the high-aluminum high-calcium frit includes, by mass percentage, IL: 1-10%, SiO2: 35-65%, Al2O3: 20-30%, Fe2O3: 0.02-0.10%, TiO2: 0.01-0.05%, CaO: 10-23%, MgO: 0.5-3%, K2O: 1-8%, Na2O: 1-10%, and BaO: 0.1-3%; A translucent glaze is applied on the surface of the translucent body; the mineral composition of the translucent glaze includes, by mass percentage, 40-60% washed kaolin, 20-30% potassium feldspar, 5-15% high-aluminum high-calcium frit, 5-15% barium carbonate, and 1-10% wollastonite; wherein the chemical composition of the high-aluminum high-calcium frit includes, by mass percentage, IL: 1-10%, SiO2: 35-65%, Al2O3: 20-30%, Fe2O3: 0.02-0.10%, TiO2: 0.01-0.05%, CaO: 10-23%, MgO: 0.5-3%, K2O: 1-8%, Na2O: 1-10%, and BaO: 0.1-3%; the specific gravity of the translucent glaze is 1.4-1.5 g / cm 3 , glaze application amount is 540~700g / m 2 ; inkjet printing a design pattern on the surface of the body after the transparent glaze is applied; A low expansion protective glaze is applied on the surface of the body after the inkjet printing design pattern; the mineral composition of the low expansion protective glaze includes: by mass percentage, kaolin 8-12%, burnt talc 10-18%, low expansion frit 45-55%, barium carbonate 5-20%, wollastonite 10-18%, calcined zinc oxide 1-3%; wherein the chemical composition of the low expansion frit includes: by mass percentage, IL: 0.1-0.5%, SiO2: 47-54%, Al2O3: 10-16%, Fe2O3: 0.01-0.05%, TiO2: 0.01-0.05%, CaO: 5-10%, MgO: 1-3%, K2O+Na2O: 3-6%, BaO: 8-12%, ZnO: 10-15%; the specific gravity of the low expansion protective glaze is 1.5-1.6 g / cm 3 , glaze application amount is 600~770g / m 2 ; The green body to which the low expansion protective glaze is applied is fired and polished to obtain the low expansion wear-resistant high light transmittance dense seam continuous pattern ceramic rock plate.

2. The preparation method according to claim 1, characterized in that The thermal expansion coefficient of the translucent glaze at 40-600°C is 6.5×10 -6 / K ~6.8×10 -6 / K.

3. The preparation method according to claim 1, characterized in that: The chemical composition of the low expansion protective glaze includes, by mass percentage, IL: 3-4%, SiO2: 47-49%, Al2O3: 11-13%, Fe2O3: 0.01-0.2%, TiO2: 0.01-0.05%, CaO: 11-14%, MgO: 4-6%, K2O: 1-3%, Na2O: 1-2%, BaO: 8-10%, and ZnO: 4-6%.

4. The preparation method according to claim 1, characterized in that The thermal expansion coefficient of the low expansion protective glaze at 40-600°C is 6.0×10 -6 / K ~6.2×10 -6 / K.

5. The preparation method according to claim 1, characterized in that: The light-transmitting glaze is applied by spraying glaze.

6. The preparation method according to claim 1, characterized in that: The low expansion protective glaze is applied by spraying glaze.

7. The preparation method according to claim 1, characterized in that: The firing temperature is 1190~1210℃, and the firing time is 60~80 minutes.

8. A low expansion, wear-resistant, high light transmittance, close-seam and continuous-grain ceramic rock plate, characterized in that: The low expansion, wear-resistant, high light transmittance, dense seam and continuous pattern ceramic rock slab is obtained according to the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Light-transmitting stone ceramic plate and preparation method thereof

    CN113800879A

  • High-transparency ceramic rock plate with deep concave-convex textures and preparation method of high-transparency ceramic rock plate

    CN114804824A

  • Close-seam and stripe-connected low-expansion-coefficient floor heating ceramic tile and preparation method thereof

    CN114988857A